Reliability of Lupus Anticoagulant and Anti-phosphatidylserine/prothrombin Autoantibodies in Antiphospholipid Syndrome: A Multicenter Study - Sciascia, Savino; Radin, Massimo; Cecchi, Irene; Rubini, Elena; Scotta, Anna; Rolla, Roberta; Montaruli, Barbara; Pergolini, Patrizia; Mengozzi, Giulio; Muccini, Emanuela; Baldovino, Simone; Ferro, Michela; et al. (Frontiers in Immunology, 2019)
Background Correct interpretation of lupus anticoagulant(LA) tests is crucial for diagnosis of Antiphospholipid Syndrome(APS). However, testing patients during vitamin K antagonist(VKA) or other anticoagulant treatment remains a contentious issue and has been discouraged by official guidelines because of interpretational problems affecting the mixing test. In this study, we aimed to evaluate the reproducibility of LA testing and to assess the diagnostic performance of phosphatidylserine/prothrombin(aPS/PT) antibodies in different clinical settings of Antiphospholipid Syndrome (APS). Methods We enrolled 60 patients who met one of the following inclusion criteria: 1)Fulfilled the diagnosis of thrombotic APS; 2)Patients with thrombosis not completely fulfilling the Sidney criteria, as follows: a)inconstant previous LA positivity; and/or b)low-medium titers aPL[defined as levels of anticardiolipin or anti-β2Glycoprotein-I(IgG/IgM)10-30 GPL/MPL aPL] with no previous evidence of LA positivity. aPL testing was performed in a blind fashion in 4 centers undergoing periodic external quality assessment. Results Out of 60 enrolled patients, 43(71.7%) presented with thrombotic APS, 7(41.2%) with thrombosis and inconstant LA positivity and 10(58.8%) with low-medium titers aPL. Categorical agreement for LA among the centers, as expressed by Cohen's kappa coefficients, ranged from 0.41 to0.60(corresponding to moderate agreement). The correlation among quantitative results determined at the 4 sites for aPS/PT IgG was strong(Spearman rho0.84). When aPS/PTIgG were dichotomized for positive vs. negative results, Cohen's kappa coefficients ranged from0.81 to 1.0). We observed 27/60(45%) of the total and15/20(75%) of the VKA treated cases with discordant LA results(as defined by lack of agreement in ≥3laboratories) or inconclusive. Conversely, in those cases, we observed a good correlation for aPS/PT IgG testing (Cohen's kappa=0.81–1, Spearman rho 0.86). aPS/PT testing showed an overall agreement of 83%(up to 90% in patients receiving VKA), providing an overall increase in test reproducibility of +28% when compared to LA, becoming even more evident (+65%) when analyzing patients on VKA. Conclusion aPS/PT testing showed an overall agreement of 83%, providing an increase in test reproducibility of +28% when compared to LA, becoming even more evident(+65%) when analyzing patients on VKA. The introduction of aPS/PT testing might represent a further diagnostic tool, especially when LA is not available or the results are uncertain.